A Dendrimer Supported Electrochemical Immunosensor for the Detection of Alpha‐feto protein – a Cancer Biomarker. Issue 1 (23rd October 2017) - Idris, Azeez O.; Mabuba, Nonhlangabezo; Arotiba, Omotayo A.
Abstract: The electrochemical detection of alpha‐feto protein based on novel gold nanoparticles‐ poly(propylene imine) dendrimer platform is reported. The platform was prepared by co‐electrodeposition of gold nanoparticles and generation 3 poly (propylene imine) dendrimer on a glassy carbon electrode. Each modifying step was characterised by cyclic voltammetry and electrochemical impedance spectroscopy. The electrochemical measurements showed that the platform was stable, conducting and exhibited reversible electrochemistry. Results obtained from the electrochemical impedance spectroscopy interrogation in [Fe(CN)6 3−/4− ] redox probe showed a marked reduction in charge transfer resistance (Rct ) after each modification step. The immunosensor was prepared by immobilisation of a probe anti‐alpha feto protein (AFP) on the platform for 3 hrs at 35 °C followed by blocking the surface with bovine serum albumin to minimise non‐specific binding. The prepared immunosensor was used to detect AFP over a wide concentration range from 0.005 to 500 ng/mL and detection limits of 0.0022 and 0.00185 ng/mL were obtained for SWV and EIS measurements respectively. The immunosensor gave good stability over a period of fourteen days when stored at 4 °C. Abstract :